2014
DOI: 10.1002/chem.201402147
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide Shells as a Decisive Factor for Moderate and Strong Ionic Interactions of Dendritic Poly(ethylene imine) Scaffolds under Shear Forces

Abstract: For better understanding and improving the non-covalent interactions of dendritic core-shell, we evaluated the interactions of hyperbranched poly(ethylene imine) (PEI) decorated with various oligosaccharide shells with water-soluble B vitamins, an estradiol derivative and pantoprazole. Depending on the different properties of the analyte molecules, dendritic core-shell glyco architectures showed (very) weak, moderate and strong interactions with the analyte molecules. Thus, ionic interactions are the strongest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The zeta-potential experiments revealed rather small values |f| < 10 mV in the investigated pH-range, suggesting minor cationic charges of the nanostructure. The importance of electrostatic interactions for the uptake of drug-like molecules to PEI-Mal structures has been reported in previous studies [22,27]. However, when it comes to the detailed structure of the PEI-Mal species the impact of pH on the SAXS curves is not detectable, which might be due to the compact structure of dendritic glycoarchitectures.…”
Section: Analysis Of Saxs Datamentioning
confidence: 84%
See 2 more Smart Citations
“…The zeta-potential experiments revealed rather small values |f| < 10 mV in the investigated pH-range, suggesting minor cationic charges of the nanostructure. The importance of electrostatic interactions for the uptake of drug-like molecules to PEI-Mal structures has been reported in previous studies [22,27]. However, when it comes to the detailed structure of the PEI-Mal species the impact of pH on the SAXS curves is not detectable, which might be due to the compact structure of dendritic glycoarchitectures.…”
Section: Analysis Of Saxs Datamentioning
confidence: 84%
“…Hyperbranched structures such as PEI and PEI-Mal species are expected to function as carriers of drugs and some studies of these systems and their interaction with model drugs have been reported [19,22,27,32]. In the present work, we have investigated the interaction between the strongly hydrophobic model drug retinol (cf.…”
Section: Interaction Between Retinol and Pei And Pei-mal Complexesmentioning
confidence: 98%
See 1 more Smart Citation
“…A mean value of about 55 nm of three scratch experiments was evaluated. Thus, the AFM measurement can be used as a direct and accurate method to detect the layer thickness because a direct AFM tip contact with the substrate and the coated surface is given . The resulted thickness was not totally away from that was detected by ellipsometry.…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of AF4 include a broad separation range accessible by a single channel and significantly reduced risk of shear degradation . The application of this method constitutes a significant extension of our previous studies on the complexation patterns of glycosylated branched polymers . The experiments have been carried out for PPI‐Mal OS G4 at pH 7.4 (physiological conditions) and 5.8 (acidic cellular compartment) ( Figure ).…”
Section: Zeta Potential Of Ppi Dendrimers and Nucleotide–dendrimer Comentioning
confidence: 99%